Persepsi kakitangan sokongan terhadap amalan pengurusan kualiti menyeluruh : kajian kes di Pejabat Residen, pejabat-pejabat Daerah Samarahan, Serian dan Simunjan - Awang Hepeni, Bin Hj. Awang (2000)
The purpose of this study was to identify the level of Total Quality Management (TQM) principles practices based on the perception of the support staff at the Resident Office, Samarahan, Serian and Simunjan District Offices (PRPDSSS). This study also attempted to find out the respondentsʼ level of knowledge on TQM principles and their level of involvement in quality activities.